The role of nurses as human papillomavirus vaccination advocates in China: perception from nursing students - Yulan Lin; Zhijian Hu; Haridah Alias; Li Ping Wong (Human Vaccines & Immunotherapeutics, 2022)
This study aimed to investigate nursing students’ perspectives regarding the role of nurses as HPV vaccine advocates and their perception of barriers to advocacy. A cross-sectional study using a Web-based survey was sent out to all undergraduate nursing students enrolled at the Fujian Medical University, Fuzhou, China. A total of 1,041 students responded to the survey. In total, 58.0% of students expressed an intent to advocate HPV vaccines as a counselor and 56.4% as an HPV information provider in their future practice. However, 33.4% stated that they do not intend to be HPV vaccine advocates. Grade 1 students, students from homes with higher annual household incomes and those with a higher level of knowledge about HPV and HPV vaccination expressed higher intentions to advocate for HPV vaccines as a counselor. Students who have a higher level of knowledge about HPV and HPV vaccination and have received HPV vaccines reported a higher advocacy intent in the provision of HPV information. The main perceived barriers in HPV vaccine advocacy include inadequate training (87.1%) and insufficient HPV-related knowledge (84.8%); also, anxious patients may not feel comfortable with nurses discussing HPV vaccination (52.8%). Nurses are uniquely positioned to nurture patient HPV vaccine acceptance and maybe the key strategy to increase HPV vaccination coverage in China. Institutional support is needed to train nurses as HPV vaccine advocates and should focus on enhancing HPV-related knowledge while destigmatising the embarrassment around discussing HPV-related issues with patients.